Assessment of in vivo skeletal muscle mitochondrial respiratory capacity in humans by near-infrared spectroscopy: a comparison with in situ measurements - Ryan, Terence E (BlackWell Publishing Ltd, 2014)
The present study aimed to compare in vivo measurements of skeletal muscle mitochondrial respiratory capacity made using near-infrared spectroscopy (NIRS) with the current gold standard, namely in situ measurements of high-resolution respirometry performed in permeabilized muscle fibres prepared from muscle biopsies. Mitochondrial respiratory capacity was determined in 21 healthy adults in vivo using NIRS to measure the recovery kinetics of muscle oxygen consumption following a ∼15 s isometric contraction of the vastus lateralis muscle. Maximal ADP-stimulated (State 3) respiration was measured in permeabilized muscle fibres using high-resolution respirometry with sequential titrations of saturating concentrations of metabolic substrates. Overall, the in vivo and in situ measurements were strongly correlated (Pearson's r = 0.61–0.74, all P < 0.01). Bland–Altman plots also showed good agreement with no indication of bias. The results indicate that in vivo NIRS corresponds well with the current gold standard, in situ high-resolution respirometry, for assessing mitochondrial respiratory capacity.